Le Programme National de Recherche Suisse « Paysages et habitats de l’Arc Alpin » - Bernard Lehmann; Paul Messerli (Revue de Géographie Alpine)
The aim of the Swiss National Research Programmes is to carry out scientific research to identify, analyse and "find solutions" to problems that are perceived by the scientific and political communities as a national challenge. This article, which deals with landscape resources in the Swiss Alpine arc, shows the stages and measures taken in managing such programmes. The article focuses on the objectives and questions underlying the research, the integration of knowledge acquired and the ways results are used in the political sphere.